2009
DOI: 10.1093/annhyg/mep059
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Polycyclic Aromatic Hydrocarbons (PAHs), Mutagenic Aldehydes, and Particulate Matter in Norwegian a la Carte Restaurants

Abstract: Working as a cook in a Norwegian à la carte restaurant with some manual panfrying involves exposure to components in cooking fumes which may cause adverse health effects. Additional studies are necessary in order to identify relations between exposure levels and the adverse health effects of cooking fumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…However, information from Statistics Sweden in 2001 regarding work-related health problems in the last 12 months, showed that work-related mental stress was not more commonly reported by cooks, waiters/waitresses or kitchen and restaurant workers compared with the total occupationally active population in Sweden (33). Among females (129 female cooks and 261 female restaurant and kitchen assistants participated), 8.4% of cooks and 6.6% of kitchen and restaurant workers reported health problems due to mental stress at work, compared with 11.2% among the total female working population.…”
Section: Discussionmentioning
confidence: 99%
“…However, information from Statistics Sweden in 2001 regarding work-related health problems in the last 12 months, showed that work-related mental stress was not more commonly reported by cooks, waiters/waitresses or kitchen and restaurant workers compared with the total occupationally active population in Sweden (33). Among females (129 female cooks and 261 female restaurant and kitchen assistants participated), 8.4% of cooks and 6.6% of kitchen and restaurant workers reported health problems due to mental stress at work, compared with 11.2% among the total female working population.…”
Section: Discussionmentioning
confidence: 99%
“…carcinogenic potency tend to bind to larger particles rather than ultrafine particles. One possible explanation for this phenomenon is that the ultrafine particles might be generated from selfnucleation of high temperature oil vapor, which had been oxidized in the air and contained lots of oxidized compounds, such as aldehydes [39,53] rather than carcinogenic PAHs.…”
Section: Pahs From Cooking Activities In Household Kitchensmentioning
confidence: 99%
“…2 3 Occupational exposures can occur in common workplace settings such as restaurants. 4 PAHs and PAH-DNA adducts have been found in placental tissues of women, amniotic fluid samples and umbilical cord blood samples from newborns. [5][6][7][8][9][10] PAH adducts can disrupt the cell's microenvironment, 1 11 to which the rapidly growing and differentiating cells of the fetus may be particularly vulnerable.…”
Section: Introductionmentioning
confidence: 99%